BioGeomancer: automated georeferencing to map the world's biodiversity data - Guralnick, Robert P.; Wieczorek, John; Beaman, Reed; Hijmans, Robert J. (Public Library of Science, 2006)
Over the past 250 years, biologists who were interested in describing and understanding patterns of biological diversity have gone into the field to observe and collect species. Conservation of the specimens and data collected through these explorations has produced an irreplaceable archive of life on Earth [1]. Today, the billions of specimens in natural history collections, such as dried plants and stuffed birds, play a fundamental role in generating new knowledge about biodiversity and in guiding its conservation. Yet, the potential of this vast store of data is much greater than is currently realized